Marital Self-Efficacy and Its Relationship with Conflict Management Styles among Couples - Jarwan, Ali Saleh; Bany Melhem, Shoroq Nazeeh (Dirasat: Educational Sciences, 2026)
Objectives: This study examined the level of marital self-efficacy and its relationship with conflict management styles among married couples. It also investigated whether statistically significant differences existed based on gender, age, duration of marriage, and educational qualification. Methods: A descriptive correlational approach was employed. The marital self-efficacy scale and the conflict management styles scale were administered to a convenience sample of 974 married individuals (husbands and wives). Results: The findings indicated a high level of marital self-efficacy among participants. No statistically significant differences were found based on duration of marriage or educational qualification. However, significant gender differences were observed in overall marital self-efficacy and in interaction with the immediate social environment, favoring males. Age-related differences were found in overall self-efficacy and marital relationship dimensions, favoring participants under 30 years of age. Levels of conflict management styles ranged from low to high, with the integrating style ranking highest and the obliging style ranking lowest. Gender differences favored males in the integrating style and females in the avoiding and dominating styles. Marital self-efficacy showed a statistically significant positive correlation with integrating and compromising styles and a negative correlation with avoiding, dominating, and obliging styles. Conclusions: The study underscores the importance of developing counseling and training programs aimed at strengthening marital self-efficacy and encouraging the use of constructive conflict management styles to enhance marital stability and relationship quality.